Retraction Note to: Co-Administration of TiO2 Nanowired Mesenchymal Stem Cells with Cerebrolysin Potentiates Neprilysin Level and Reduces Brain Pathology in Alzheimer’s Disease (Molecular Neurobiology, (2018), 55, 1, (300-311), 10.1007/s12035-017-0742-9) - Sharma H.S.; Muresanu D.F.; Lafuente J.V.; Patnaik R.; Tian Z.R.; Ozkizilcik A.; Castellani R.J.; Mössler H.; Sharma A. (My University, 2025)
The Editor-in-Chief has retracted this article because of concerns regarding the figures presented in this work. These concerns call into question the article's overall scientific soundness. An investigation conducted after its publication discovered the following issues: The bottom left corner of Panel c of Fig. 1 appears to overlap with a portion of the top right corner of Panel d of the same figure; The top half of Panel a of Fig. 2 appears to overlap with the bottom half of Panel b of the same figure; The top half of Panel b of Fig. 2 appears to overlap with the bottom half of Panel c of the same Figure; The top half of Panel c of Fig. 2 appears to overlap with the bottom half of Panel f of the same figure. The bottom left corner of Panel c of Fig. 1 appears to overlap with a portion of the top right corner of Panel d of the same figure; The top half of Panel a of Fig. 2 appears to overlap with the bottom half of Panel b of the same figure; The top half of Panel b of Fig. 2 appears to overlap with the bottom half of Panel c of the same Figure; The top half of Panel c of Fig. 2 appears to overlap with the bottom half of Panel f of the same figure. These panels represent different types of tissue or tissues taken from animals which underwent different treatments. The Editor-in-Chief therefore no longer has confidence in the integrity of the research presented in this article. Hari Shanker Sharma and Aruna Sharma disagree with this retraction. Dafin Fior Muresanu, José Vicente Lafuente, Ranjana Patnaik, Z. Ryan Tian, Asya Ozkizilcik, and Herbert Mössler have not replied to correspondence from the Publisher. Rudy J. Castellani, who is listed as a co-author of this article, has stated that he did not participate in the research reported therein and that his name and affiliation were added to the author list without his consent. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.